Humanidades em revista: reflexões sobre a cobertura jornalística das ciências do homem - Jurandira Fonseca Gonçalves (2013)
This dissertation seeks to analyze the journalistic coverage of the humanities in specialized magazines that propose formally to talk about science. To do so, turn to how the humanities are theme or themed in stories of four science magazines, in order to understand the statute they occupy forward to these publications and how gesture and journalistic rhetoric are directed to the issue and propose representations. The publications were divided into two categories: popular (Superinteressante and Galileo) and institutional (Minas Faz Ciência and Pesquisa Fapesp). This effort is developed through the perspectives that the study of cover articles of such publications throughout 2011, offers. To make this, we start with a discussion about dissemination of science and scientific journalism in general, as a means of thinking about the context in which the coverage of the humanities is a part, and focus on the place of the humanities in the body of science. We turn, then, to how the specific dimensions of the human sciences are approached, in order to understand how the magazines deal with that. The work is based on the premise that the humanities achieve practical application in circulation, or reach their "effects" through its dissemination and integration into practical life, in their ability to "infiltrate" and influence the forms of people act and think (RIBEIRO, 2003). Two ideas form the land where the present proposal falls: the notion that it is in the communicative process, social practices of interaction, that science is constituted, is participated and shared; and the fact that the public communication of science contributes not only for the dissemination of scientific knowledge, but affects the social and cultural landscape of individuals and is related to the proper functioning of democracy.